2012
DOI: 10.5194/nhess-12-2311-2012
|View full text |Cite
|
Sign up to set email alerts
|

Active faults and historical earthquakes in the Messina Straits area (Ionian Sea)

Abstract: Abstract. The Calabrian Arc (CA) subduction complex is located at the toe of the Eurasian Plate in the Ionian Sea, where sediments resting on the lower plate have been scraped off and piled up in the accretionary wedge due to the African/Eurasian plate convergence and back arc extension. The CA has been struck repeatedly by destructive historical earthquakes, but knowledge of active faults and source parameters is relatively poor, particularly for seismogenic structures extending offshore. We analysed the fine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 68 publications
2
57
0
Order By: Relevance
“…The dip then increases again at a depth of 50 km, more or less beneath the Tyrrhenian coast. Constraints on the slab interface geometry in this area are provided essentially by seismic profiles (Finetti, 2005;Minelli and Faccenna, 2010;Polonia et al, 2011Polonia et al, , 2012. V p and V s tomography reveals the presence of a high velocity anomaly beneath the Tyrrhenian Sea as deep as 600 km (Piromallo and Morelli, 2003;Chiarabba et al, 2008;Giacomuzzi et al, 2011).…”
Section: Subduction Fault Source (Type 1)mentioning
confidence: 99%
See 2 more Smart Citations
“…The dip then increases again at a depth of 50 km, more or less beneath the Tyrrhenian coast. Constraints on the slab interface geometry in this area are provided essentially by seismic profiles (Finetti, 2005;Minelli and Faccenna, 2010;Polonia et al, 2011Polonia et al, , 2012. V p and V s tomography reveals the presence of a high velocity anomaly beneath the Tyrrhenian Sea as deep as 600 km (Piromallo and Morelli, 2003;Chiarabba et al, 2008;Giacomuzzi et al, 2011).…”
Section: Subduction Fault Source (Type 1)mentioning
confidence: 99%
“…Recent seismic profile interpretations Van Dijk et al, 2000;Finetti, 2005;Minelli and Faccenna, 2010;Polonia et al, 2011) revealed that the accretionary wedge internal structure has two distinct lobes, the eastern lobe and western lobe, affected by large splay faults [C2-C6] deemed to be potentially seismogenic by Polonia et al (2011Polonia et al ( , 2012. These splay faults reach the subduction plane at a depth of 15-20 km in the eastern lobe and around 12 km in the western lobe with NW dipping plane of less than 20 ‱ .…”
Section: Crustal Fault Sources (Type 1): Calabrian Accretionary Wedgementioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the nature and origin of the Ionian basin crust is still a matter of debate (e.g. Polonia et al 2012;Gallais et al 2013). Due to its regional importance as a deep-seated weakness zone, a link between the Malta Escarpment and Mt E ' f c h b , as the maximum uplift rates in the regional setting of Mt Etna are related to the upthrown side of the Malta Escarpment (Rust and Kershaw, 2000).…”
Section: 1tectonic Setting Of Mt Etnamentioning
confidence: 99%
“…Examples of similar documented events in other parts of the world where the seismic activity is too low are given in Polonia et al (2012), Vipin et al (2009) andDel Gaudio et al (2009). In this study we present a detailed analysis of the seismic source parameters of events of the Peñamiller sequence, monitored during the first three months of 2011.…”
Section: Introductionmentioning
confidence: 99%